Vibration Stimulation to Increase Milk Production in Puerperal Mothers - Raraswati, Rhela Panji; Wijayanti, Krisdiana; Hendriyani, Heni (JURNAL INFO KESEHATAN, 2024)
Breast milk is the best food for babies, but insufficient production can hinder breastfeeding. Many mothers face challenges with milk production, preventing optimal breastfeeding. This study aims to innovate and develop a vibration-based electric massage device to enhance breast milk production and analyze its effectiveness based on baby weight indicators. The research employs a quantitative method with a Quasi-Experimental design, divided into an intervention group and a control group. A random sampling technique selected 46 respondents, split evenly between the two groups. The intervention group received breast care using the vibration-based device, while the control group received standard breast care for 14 days. Breast care was administered twice daily for 2-3 minutes. Baby weight was measured at 14, 21, and 28 days. Tools to measure energy intake, protein intake, and fluid intake utilized food recall, and breastfeeding frequency was measured by a scale. Psychological status was assessed using the DASS questionnaire. Data analysis included Repeated Measure ANOVA and Independent Simple T-Test. Results indicated a significant difference in breast milk production based on baby weight between the intervention and control groups (p=0.000). The mean weight difference between the groups was 200.21 grams, favoring the intervention group. Increased breast milk production was not influenced by confounding variables such as energy intake, protein intake, fluid intake, breastfeeding frequency, and psychological status. In conclusion, the developed vibration-based electric massage device effectively increased breast milk production, evidenced by significant weight gain in babies within the intervention group compared to the control group (p=0.000).